THE SEPARATION OF CRIMINAL PROCEDURAL FUNCTIONS - Kaija, Sandra (Administrative and Criminal Justice, 2017)
The term criminal procedural function has historically been used by scientists. In order to identify primary issues in procedural functions, the competition principle was analyzed. This strengthened such important issues as separation of prosecution and court functions, parties’ equality, independence of courts etc. Therefore, the concept of three concept functions – prosecution, defence and adjudication – was developed in criminal proceedings.  In the context of the Criminal Procedure Law having taking effect, this term was included into the law, including the principle of separation of criminal procedural functions.The aim of this paper is to offer the insight into interpretation of the concept of the criminal procedural function with the special focus on specific issues in function separation. Section 17 of Criminal Procedure Law determines the function of control of restrictions of human rights in a pre-trail. The functions of prosecution, defence and adjudication do not determine their priority over all other criminal procedural functions. These functions are claimed to be separate and therefore cannot be applied to the same person.